2013
DOI: 10.1371/journal.pone.0070740
|View full text |Cite
|
Sign up to set email alerts
|

An NO Donor Approach to Neuroprotective and Procognitive Estrogen Therapy Overcomes Loss of NO Synthase Function and Potentially Thrombotic Risk

Abstract: Selective estrogen receptor modulators (SERMs) are effective therapeutics that preserve favorable actions of estrogens on bone and act as antiestrogens in breast tissue, decreasing the risk of vertebral fractures and breast cancer, but their potential in neuroprotective and procognitive therapy is limited by: 1) an increased lifetime risk of thrombotic events; and 2) an attenuated response to estrogens with age, sometimes linked to endothelial nitric oxide synthase (eNOS) dysfunction. Herein, three 3rd generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 93 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…Loss is considered to have occurred if the animal remains on its back for more than 30 s. Righting reflex is considered to be regained when the mice were able to successfully right themselves with all four paws touching the floor, twice within 20 s [ 81 ]. Step through passive avoidance (STPA) STPA has been widely used to test long-term working memory and was performed as we have previously described [ 82 85 ]. Each animal was given two ip injections: (1) Amnesic agent (scopolamine 1 mg/kg, MK-801 0.1 mg/kg, diazepam 0.5 mg/kg, L-NAME 50 mg/kg) or saline were given 30 min prior to training plus NMZ or saline in the time and delivery method as indicated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Loss is considered to have occurred if the animal remains on its back for more than 30 s. Righting reflex is considered to be regained when the mice were able to successfully right themselves with all four paws touching the floor, twice within 20 s [ 81 ]. Step through passive avoidance (STPA) STPA has been widely used to test long-term working memory and was performed as we have previously described [ 82 85 ]. Each animal was given two ip injections: (1) Amnesic agent (scopolamine 1 mg/kg, MK-801 0.1 mg/kg, diazepam 0.5 mg/kg, L-NAME 50 mg/kg) or saline were given 30 min prior to training plus NMZ or saline in the time and delivery method as indicated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, diverse experiments subsequently confirmed a role of raloxifene inducing endothelium-dependent relaxation as due to the upregulation of nitric-oxide synthase (eNOS) expression [ 38 , 39 , 40 ]. Although these results can be due to the partial agonist profile of raloxifene reported in this work [ 33 ], the effect can also be explained as due to the activation of the GPR30 receptor [ 41 ]. Accordingly, further experimental work is necessary to differentiate both effects.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, in another study (Bolego et al, ) in female rat aorta, it was found that the relaxant responses to 17β‐estradiol or the ERα agonist 4,4′,4″‐(4‐propyl‐[1H]pyrazole‐1,3,5‐triyl) tris‐phenol were endothelium‐dependent. Moreover, in male rat aorta, three different SERM agonists, raloxifene, desmethylarzoxifene (DMA) and NO‐DMA, showed similar potency at inducing relaxation, and this effect of DMA was dose‐ and endothelium‐dependent (VandeVrede et al, ). Also, raloxifene at 1 μM has been shown to inhibit iNOS expression and NO levels induced by cytokines in rat aortic smooth cells, effects reversed by specific ERα inhibitors (Pinna et al, ).…”
Section: Discussionmentioning
confidence: 99%